TRADITIONS AND CUSTOMS RELATED TO EMBROIDERY (Conferencea, 2022)
Depending on the embroidery, embroidery is divided into hats, shoes, outerwear, and embroidery. It is also worth mentioning the embroidery that is now sewn on shoes. This in turn embroidered on the clothes serves their solemnity and luxury. Embroidery is mainly sewn for home decorations. Large embroideries, on the other hand, were associated with the happiest and happiest moments of a girl’s life. The bride-to-be sewed and embroidered large and small embroideries of various patterns, mainly for her future family. Almost every family was engaged in embroidery for their own needs. That is why in every family of Shakhrisabz a growing girl is taught.